Dual signal transduction pathways activated by TSH receptors in rat primary tanycyte cultures - Bolborea, Matei; Helfer, Gisela; Ebling, Francis J.P.; Barrett, Perry (Bioscientifica, 2015)
Tanycytes play multiple roles in hypothalamic functions, including sensing peripheral nutrients and metabolic hormones, regulating neurosecretion and mediating seasonal cycles of reproduction and metabolic physiology. This last function reflects the expression of TSH receptors in tanycytes, which detect photoperiod-regulated changes in TSH secretion from the neighbouring pars tuberalis. The present overall aim was to determine the signal transduction pathway by which TSH signals in tanycytes. Expression of the TSH receptor in tanycytes of 10-day-old Sprague Dawley rats was observed by in situ hybridisation. Primary ependymal cell cultures prepared from 10-day-old rats were found by immunohistochemistry to express vimentin but not GFAP and by PCR to express mRNA for Dio2, Gpr50, Darpp-32 and Tsh receptors that are characteristic of tanycytes. Treatment of primary tanycyte/ependymal cultures with TSH (100 IU/l) increased cAMP as assessed by ELISA and induced a cAMP-independent increase in the phosphorylation of ERK1/2 as assessed by western blot analysis. Furthermore, TSH (100 IU/l) stimulated a 2.17-fold increase in Dio2 mRNA expression. We conclude that TSH signal transduction in cultured tanycytes signals via Gαs to increase cAMP and via an alternative G protein to increase phosphorylation of ERK1/2.